Alarmingly high prevalence of smoking and symptoms of bronchitis in young women in Sweden: a population-based questionnaire study - Wennergren, Göran (Prim Care Respir J, 2013)
BACKGROUND: After 10 years of a decrease in smoking among young people in Sweden, we now have indications of increased smoking. AIMS: To provide up-to-date information on the prevalence of smoking and smoke-associated respiratory symptoms in young adults in Sweden, with a special focus on possible gender differences. METHODS: In the West Sweden Asthma Study, a detailed postal questionnaire focusing on asthma, respiratory symptoms, and possible risk factors was mailed to 30,000 randomly selected subjects aged 16–75 years. The analyses are based on responses from 2,702 subjects aged 16–25 years. RESULTS: More young women than men were smokers (23.5% vs. 15.9%; p<0.001). Women started smoking earlier and smoked more. Symptoms such as longstanding cough, sputum production, and wheeze were significantly more common in smokers. In the multiple logistic regression analysis, smoking significantly increased the risk of recurrent wheeze (odds ratio (OR) 2.0 (95% CI 1.4 to 3.0)) and sputum production, (OR 2.4 (95% CI 1.9 to 3.1)). CONCLUSIONS: The alarmingly high prevalence of smoking among young women was parallel to a similarly high prevalence of bronchitis symptoms. This is worrisome, both in itself and because maternal smoking is a risk factor for illness in the child. Adverse respiratory effects of smoking occur within only a few years of smoking initiation.